ANALISIS RASIO PROFITABILITAS DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yanti, Juli; Tipa, Handra (LPPM Universitas Putera Batam, 2021)
The purpose of this study is to determine whether the ratio of profitability and liquidity has an effect on financial performance in companies listed on Indonesia Stock Exchange for 2015-2019 period. The population in this study are food and beverage companies were 31 companies listed on Indonesia Stock Exchange and the sampling technique used purposive sampling technique so that the samples obtained were 11 companies. The method of this study uses horizontal analysis method. The conclusion in this study are based on profit margin in food and beverage companies, there are 1 company that has good financial performance and 10 companies that have poor financial performance. Based on Return on Assets (ROA) in food and beverage companies, there are 11 companies that have poor financial performance. Based on Return on Equity (ROE) in food and beverage companies, there are 11 companies that have poor financial performance. Based on current ratio in food and beverage companies, there are 7 companies that have good financial performance and 4 companies that have poor financial performance. Based on quick ratio in food and beverage companies, there are 6 companies that have good financial performance and 5 companies that have poor financial performance.